Overview of Health Impacts due to Haze Pollution in Johor, Malaysia - Nur H. Hanafi; Mimi Haryani Hassim; Zainura Z. Noor (Journal of Engineering and Technological Sciences, 2018)
Haze pollution is one of the major environmental issues caused by aerosols, having brought about a history of heavy smog pollution events like the London smog in 1952 and the Los Angeles smog in the 1960s. However, in Malaysia, haze events are attributed to forest and peat fires in Kalimantan and Southern Sumatra, Indonesia. The burned biomass basically contains concentrated particulate matters that are hazardous to health among susceptible population groups. Based on the extensive literature review conducted, the small number of available local studies on the health effects of air pollution in Malaysia conducted so far focused on air pollution sciences. In this paper, a comprehensive overview of studies done on the impacts of haze on health conditions among populations in Malaysia is presented. The result shows that the number of upper respiratory tract infection cases was directly proportional to the particulate matter concentration and Air Pollution Index value in Johor in the years 2014 and 2015. Particulate matteris the major contributor in the formation of heavy hazes and is more likely to initiate detrimental health effects compared to other inhalable particles due to their size, large area, and strong activity, making them more likely to carry harmful substances causing a higher number of infected patients with upper respiratory tract infections.